Enantioselective addition-alkylation reactions via bisguanidinium silicate ion pair catalysis - Chen, Wen Chao (Nanyang Technological University, 2020)
The aim of this research work is to further develop the application of hypervalent silicates in highly enantioselective reactions via asymmetric ion-pairing catalysis. In this thesis, the project revealed the novel enantioselective reduction-addition strategy as an excellent synthetic methodology, and the essence of chemistry was studied mechanistically. The first chapter (Chapter 1) introduced the background from two aspects, including the introduction of asymmetric ion-pairing catalysis and the application of hypervalent silicon species in stereoselective synthesis. The following chapter presented the research project utilizing our designed enantioselective reduction-addition strategy. Since the last few years, our group has developed a series of chiral quaternary ammonium phase-transfer catalysts, which were successfully applied in asymmetric phase-transfer catalysis. Meanwhile, asymmetric ion pair catalysis was put forward as a branched subject in this field. Motivated by the concept of ion-pairing, the work described in this thesis proved the potential application of the bisguanidinium silicate ion pair in asymmetric catalysis. In Chapter 2, the high enantioselective reduction-alkylation and reduction-addition of chromones and coumarins was realized through bisguanidinium silicate ion-pairing catalysis. The active hypervalent silicate intermediates were characterized by NMR spectroscopy, control experiments and supported by computational data. Chapter 3 is the detailed mechanistic study. Chapter 4 is the experimental procedures and characterization data of the chiral products.